Differentiate x^(1/2)ln(3x) with respect to x.

First we notice that this is a product of two functions of x, so we are going to use the product rule. Recall (uv)'(x)=u'(x)v(x)+v'(x)u(x). Let u(x)=x^(1/2) and v(x)=ln(3x). We need to find u'(x) and v'(x). We have that u'(x)=(1/2)x^(-1/2) by simple differentiation. Also v'(x)=3/3x=1/x by applying the chain rule. Therefore (uv)'(x)=(1/2)x^(-1/2)*ln(3x)+(1/x)*x^(1/2)=(1/2)x^(-1/2)ln(3x)+x^(-1/2)=x^(-1/2)((1/2)ln(3x)+1), simplifying it down to its simplest form.

Answered by Aidan R. Maths tutor

9453 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

Find (dy/dx) of x^3 - x + y^3 = 6 + 2y^2 in terms of x and y


f(x) = 2 / (x^2 + 2). Find g, the inverse of f.


Given that y = exp(2x) * (x^2 +1)^(5/2), what is dy/dx when x is 0?


Given two functions x = at^3 and y = 4a, find dy/dx


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences